2016
DOI: 10.1111/mec.13793
|View full text |Cite
|
Sign up to set email alerts
|

Specific alleles at immune genes, rather than genome‐wide heterozygosity, are related to immunity and survival in the critically endangered Attwater's prairie‐chicken

Abstract: The negative effects of inbreeding on fitness are serious concerns for populations of endangered species. Reduced fitness has been associated with lower genome-wide heterozygosity and immune gene diversity in the wild; however, it is rare that both types of genetic measures are included in the same study. Thus, it is often unclear whether the variation in fitness is due to the general effects of inbreeding, immunity-related genes or both. Here, we tested whether genome-wide heterozygosity (20 990 SNPs) and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 107 publications
(220 reference statements)
4
64
2
Order By: Relevance
“…Also in captive-bred prairie-chicken, Bateson et al . 52 found that post release survival as well as immune responses at the time of release were related to specific MHC alleles.…”
Section: Discussionmentioning
confidence: 98%
“…Also in captive-bred prairie-chicken, Bateson et al . 52 found that post release survival as well as immune responses at the time of release were related to specific MHC alleles.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the genes themselves could be diverse, or alternatively, they might be related mainly to immunity, with reduced parasite loads and disease leading to greater longevity, enhanced growth, behavioral dominance and attractiveness. There is some evidence to suggest that immune genes do play a disproportionate role, in at least some cases (Luikart, Pilgrim, Visty, Ezenwa, & Schwartz, ; Banks, Dubach, Viggers, & Lindenmayer, ; Assunção‐Franco, Hoffman, Harwood, & Amos, ; Lenz, Mueller, Trillmich, & Wolf, ; Bateson et al, ; Ferrer, García‐Navas, Sanz, & Ortego, ; Brambilla, Keller, Bassano, & Grossen, ). However, in general, it has proven difficult to disentangle the contributions of different genes because the vast majority of studies use neutral microsatellites, whereas studies using markers mined from functional genomic regions (Da Silva et al, ; Olano‐Marin, Mueller, & Kempenaers, ; Laine, Herczeg, Shikano, & Primmer, ; Ferrer et al, ) are still relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The third, biologically motivated interpretation relied on the fitness value of MHC alleles, which was estimated relying on the strength of association between the presence of allele and longevity. If a particular allele implies parasite resistance (or susceptibility), individuals that harbour these alleles should realize higher (or lower) survival and live longer than individuals that do not have the allele (e.g., Bateson et al., ; Brouwer et al., ; Lukasch et al., ; Paterson, Wilson, & Pemberton, ; Sepil, Lachish, & Sheldon, ). Correspondingly, we tested for the association of each allele with lifespan (estimated as the oldest age in our long‐term ringing records) in a t test, from which the derived statistic was converted into an effect size ( r ).…”
Section: Methodsmentioning
confidence: 99%